Increased Durability of Concrete Against High Temperatures due to Fire using Vermiculite and Polypropylene Additives - Lintang Dian Artanti; Aulia Choiri Windari; Agastyasa Ghea Amarta (Department of Civil Engineering, Politeknik Negeri Bandung, 2024)
As a primary material in infrastructure construction, concrete must endure diverse environmental conditions and weather, including maintaining its strength when subjected to high temperatures, especially during fire-related disasters. To address this challenge, additional materials are required in the concrete mixture to enhance its resistance to high temperatures. In this study, vermiculite and polypropylene were chosen as the additives. Vermiculite was added to the concrete mix at a proportion of 36%, and polypropylene at 1%. A fire simulation was conducted by placing 28-day-old concrete specimens in a flame for 1 hour, 2 hours, and 4 hours. After the fire simulation, the results showed that concrete with the addition of vermiculite and polypropylene experienced a strength reduction of 25.76% (1 hour), 45.02% (2 hours), and 66.29% (4 hours), whereas the control concrete exhibited strength reductions of 29.43% (1 hour), 41.02% (2 hours), and 68.63% (4 hours). Therefore, it can be concluded that concrete with 36% vermiculite and 1% polypropylene is effective in maintaining 2.34% more strength. This improvement is attributed to the fact that the concrete with vermiculite and polypropylene has more voids, which effectively facilitate the circulation of trapped heat within the concrete, thereby slightly reducing the extent of damage